The Effectiveness of Local Wisdom in Landslide Disaster Management (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Every community group, even when coping with landslides, has the skills and ways to cope with the environment for its survival. This understanding and approach is referred to as